Development of PPKn learning module based on Surabaya local wisdom to improve student's learning achievement on social cultural diversity materials in Class IV at SDN Kandangan I/121 Surabaya - Sutrisno Sutrisno; Sarmini Sarmini; Nanik Setyowati (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This study aims to (1) produce a Civics learning module based on local wisdom in Surabaya to improve student achievement in fourth-grade elementary school; (2) describe the validity, practicality, and effectiveness of the Civics learning module based on local wisdom in Surabaya to improve learning achievement in the material "Socio-Cultural Diversity". This research is development research that refers to the analysis, design, development, implementation,  and evaluation  (ADDIE) development model. Data collection techniques were carried out by observing, distributing questionnaires, and administering tests. Data analysis technique using quantitative descriptive analysis techniques consisting of the validity of learning tools, analysis of student activities, analysis of the implementation of lesson plans, and learning achievement tests. Learning tools with Civics learning modules are then validated by experts. The results of expert validation stated that the learning tools with the Civics learning module were valid to be used. Then it was tested on fourth-grade students at SDN Kandangan I/121 Surabaya with pre-test and post-test. The results of field trials show (1) learning devices with the developed Civics learning module are categorized as very valid with an average score of 3.73; (2) the practical developed learning tools are based on the implementation of the lesson plans which are categorized as very good with an average implementation percentage of 93.75% and the achievement of student activities which are categorized as very well implemented with an average implementation percentage of 92.31%; (3) effective learning tools developed based on the results of students' learning achievement tests which showed that the N-Gain of 32 students was in the high category with an average of 0.72. It can be concluded that the Civics learning module based on local wisdom in Surabaya is feasible and can improve the learning achievement of fourth-grade students at SDN Kandangan I/121 Surabaya.